2015
DOI: 10.1097/nan.0000000000000125
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Vein Diameter for Peripherally Inserted Central Catheter (PICC) Insertion

Abstract: Choosing an appropriately sized vein reduces the risk of venous thromboembolism associated with peripherally inserted central catheters. This observational study described the diameters of the brachial, basilic, and cephalic veins and determined the effect of patient factors on vein size. Ultrasound was used to measure the veins of 176 participants. Vein diameter was similar in both arms regardless of hand dominance and side. Patient factors-including greater age, height, and weight, as well as male gender-wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 30 publications
0
21
0
2
Order By: Relevance
“…A projection shift occurred when yellow lines overlap the blue lines. Since the vein diameter for IV access (cephalic veins) is range from 1.5 to 6 mm [25], a simulated vein size was set to 3.75 mm (median value). Figure 6(b) shows the projection shift that can still be tolerated.…”
Section: Results Of Back-projection On Various Surface Objectsmentioning
confidence: 99%
“…A projection shift occurred when yellow lines overlap the blue lines. Since the vein diameter for IV access (cephalic veins) is range from 1.5 to 6 mm [25], a simulated vein size was set to 3.75 mm (median value). Figure 6(b) shows the projection shift that can still be tolerated.…”
Section: Results Of Back-projection On Various Surface Objectsmentioning
confidence: 99%
“…Success rate in older age is associated with central vein stenosis or exhaustion of peripheral veins. Sharp et al [24] reported that the male sex was associated with increased vein diameter. Relatively smaller vein diameter in female sex can lead to the possibility of tip malposition.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the scale in Fig. 2.1 provides a guide for determining the most appropriate catheter for vein size (Sharp et al 2015a(Sharp et al , b, 2016). • Path: Note any aberrancy along the course of the vessel (tortuosity), areas of dilation, or stenosis.…”
Section: Ultrasound Assessment Of the Patientmentioning
confidence: 99%